The business of sustainable tourism development and management - Slocum, Susan L.; Aidoo, Abena; McMahon, Kelly 1969- (Routledge, 2020)
"The Business of Sustainable Tourism Development and Management provides a comprehensive introduction to sustainable tourism, crucially combining both theoretical and practical approaches to equip students with the tools to successfully manage a sustainable tourism business or destination. Covering a range of crucial topics such as mass tourism, alternative tourism, human capital management and many more, this book incorporates a global curriculum that widens the sustainable tourism debate to include theoretical perspectives, applied research, best-practice frameworks, business tools, and case studies, facilitating a more comprehensive sustainable tourism educational strategy. Information on how to effectively implement strategies that can be applied to business environments, entrepreneurship, and job skills to enhance career preparation is at the forefront of this textbook. Highly illustrated and with an interactive companion website including bonus learning materials, this is the ideal textbook for students of tourism, hospitality, and events management at both undergraduate and postgraduate levels"-- Provided by publisher.